2009
DOI: 10.1136/bjo.2008.147819
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomised comparison of external dacryocystorhinostomy with and without silicone intubation

Abstract: DCR without silastic intubation is less expensive than DCR with silastic intubation in primary uncomplicated NLDO, and has a similar success rate. DCR with silastic intubation may create increased burden for patients in the form of more post-surgical follow-up visits. In cases of uncomplicated primary NLDO, the use of silastic intubation in DCR may be unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 14 publications
4
35
2
Order By: Relevance
“…Much of this has been made possible by the development of the technique of transcanalicular laser DCR (Narioka et al, 2008). On purpose to increase the success rate of the procedure, the use of silicone tubes in DCR is quite common (Bousch et al, 1994;Rosen et al, 1997), although its beneficial effects have not been proven unequivocally (Smirnov et al, 2008;Saiju et al, 2009;Feng et al, 2011). On the contrary, silicone intubation has its own set of complications, which includes the infective potential of these stents (Smirnov et al, 2008;Saiju et al, 2009;Feng et al, 2011;Allen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this has been made possible by the development of the technique of transcanalicular laser DCR (Narioka et al, 2008). On purpose to increase the success rate of the procedure, the use of silicone tubes in DCR is quite common (Bousch et al, 1994;Rosen et al, 1997), although its beneficial effects have not been proven unequivocally (Smirnov et al, 2008;Saiju et al, 2009;Feng et al, 2011). On the contrary, silicone intubation has its own set of complications, which includes the infective potential of these stents (Smirnov et al, 2008;Saiju et al, 2009;Feng et al, 2011;Allen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some controversies associated with this procedure in techniques with flaps, 14,15,22,23 and no study has verified the efficacy of stents in ex-DCR without flap anastomosis. Premature stent loss did not cause recurrence in the current study, and another study of ex-DCR without flap anastomosis without stent insertion also showed a success rate similar to that of the current study.…”
Section: Discussionmentioning
confidence: 97%
“…Saiju and colleagues1 carried out a study to address the important issue of whether silicone intubation is necessary in external dacryocystorhinostomy (DCR) surgery. They concluded that DCR without silastic intubation is less expensive than DCR with silastic intubation in primary uncomplicated NLDO and has a similar success rate.…”
mentioning
confidence: 99%